Implications of Heat Treatment and Systemic Delivery of Foliar-Applied Oxytetracycline on Citrus Physiological Management and Therapy Delivery - Vincent, Christopher; Pierre, Myrtho; Li, Jinyun; Wang, Nian (Frontiers in Plant Science, 2019)
Huanglongbing is an economically devastating disease of citrus in Florida and around the world. This study was undertaken to assess two grower-used therapies, heat treatment and foliar anti-bacterial application. Specifically, there was an industry claim that heat treatment improved subsequent systemic uptake of foliar-applied anti-bacterial compounds. We hypothesized that new vegetative growth induced by heat treatment could lead to increased foliar delivery because of a greater number of new leaves in which cuticles would be more permeable. The study included two factors (1.) heat treatment (with or without) and (2.) pruning, in which all new leaves, all mature leaves, or no leaves were removed. A commercial formulation of oxytetracycline (OTC) was applied to plants with a nonionic penetrant surfactant, but one branch on each tree was covered to assess direct versus systemic delivery. The study was repeated twice, destructively assessing whole-plant leaf area and dry weights, as well as OTC content in directly applied and covered leaves. Heat treatment and defoliation treatments reduced growth, but did not affect systemic delivery of OTC. OTC was detected in nearly all covered leaf samples in both repetitions, though at lower concentrations than in directly applied leaves. We conclude that neither heat treatment nor leaf age strongly affect systemic OTC delivery. Implications of this study for leaf age effects on foliar delivery and for phloem delivery of foreign compounds through foliar application are discussed.